Theories of justice and an HIV/AIDS health care policy for South Africa : a comparative analysis - Horn, Lynette (Lynette Margaret) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--University of Stellenbosch, 2003.